ANALISIS PENGARUH EKSPOR DAN IMPOR RERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - B0111068, ZAINUL MARDAWA (Jurnal Pembangunan dan Pemerataan, 2014)
This study is entitled â€œ An Analysis of the Influence of Exports and Import on Economic Growth in Indonesiaâ€. This aims of this research is to find out and analyzes the influence of fluctuations in the export value and the import value on economic growth in indonesia. In this study, the author uses descriptive-quantitative methods are used to seeing the influence or the relationship between the variables is free (value of exports and imports value) of a variable is bound (economic growth) which are then processed to obtain a conclusion. The Model used in this study is a multiple regression model with statistical analysis tools that use statistical tests, test the Hypothesis of F (t-test) and Koefesien test of Determination (R2). From the results of the analysis performed statistical tests demonstrate the value F 0.004238, with significant Î± = 0.05. significant show that exports and imports together is significantly affect the economic growth in Indonesia. While based on Hypothesis Test (test t), obtained that export variables (X 1) and imports (X 2) these two variables are affect significantly to economic growth in Indonesia. Based on the test of koefesien determination (R2) retrieved Adjusted R-Squared of 0,274766. that means exports and imports affects economic growth in Indonesia 27,74 % while the rest remaining influence by other variables analyzed in the model. To that end, the Government should make a policy so that export and import is done more efficiently so as to affect significantly to economic growth. Â  Keywords: Exports, Imports, Economic Growth